New matrix metalloproteinase inhibitors based on γ-fluorinated α-aminocarboxylic and α-aminohydroxamic acids. Issue 13 (1st July 2015) - Behrends, Malte; Wagner, Stefan; Kopka, Klaus; Schober, Otmar; Schäfers, Michael; Kumbhar, Sadhana; Waller, Mark; Haufe, Günter
Graphical abstract: Abstract: Matrix metalloproteinases (MMPs) are involved in a number of physiological as well as pathological processes such as atherosclerosis and tumorigenesis, where an up-regulation of MMPs is predominant. Fluorinated analogues of the hydroxamate-based non-peptidic broad-spectrum MMP inhibitor (MMPI) CGS 27023A were synthesized and inhibition potencies for MMP-2 and MMP-9 in the nanomolar range were measured using fluorimetric in vitro assays. The inhibition potencies of the herein reported fluorinated MMPIs were comparable or even superior in some cases to their non-fluorinated analogues. In contrast to the lead structure, both enantiomers of fluorinated MMPs were almost equally potent. Modelling studies suggest that the core α-amino hydroxamic acid residues appear to influence the relative potencies via specific inhibitor-peptidase interactions, including short fluorine–hydrogen contacts, within the enzyme's pockets. The binding of the essential hydroxamate group to the zinc ion is rather unaffected by the rest of the molecule. In contrast, the corresponding α-aminocarboxylic acid derivatives are 10 3 times less potent or were even inactive.